2022
DOI: 10.15406/sij.2022.06.00295
|View full text |Cite
|
Sign up to set email alerts
|

Looking at the no child left behind policy: the implementers’ perspectives

Abstract: This qualitative-phenomenological research aimed to determine the perspectives of the teacher-implementers about the No Child Left Behind Policy in Bato National High School. Participants of the study were three TLE teachers and five teachers from different courses. Participants were chosen through purposive sampling. Using the focus group discussions and in-depth interviews, the researchers found out that the teachers had positive and negative perceptions of the policy; it aided low-performing and at-risk stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…The NCLB Policy emphasizes the need to provide equitable opportunities for learning, growth, and development of every child without consideration of their backgrounds. It underscores that the unique one-size-fits-all approach of traditional education could be excluding a critical demographic from ideal educational opportunities (Rebusa et al, 2022). It is this commitment to inclusivity and equity, supported by legislation that provides the basis for the policy.…”
Section: Empowerment Of Philippine Literacy Education Through No Chil...mentioning
confidence: 99%
See 1 more Smart Citation
“…The NCLB Policy emphasizes the need to provide equitable opportunities for learning, growth, and development of every child without consideration of their backgrounds. It underscores that the unique one-size-fits-all approach of traditional education could be excluding a critical demographic from ideal educational opportunities (Rebusa et al, 2022). It is this commitment to inclusivity and equity, supported by legislation that provides the basis for the policy.…”
Section: Empowerment Of Philippine Literacy Education Through No Chil...mentioning
confidence: 99%
“…The policy is directly concerned in ensuring that all Filipino children receive the same opportunities to learn and become literate (Maligalig et al, 2010). Hence, this policy states that literacy education that is open for all is pivotal in transforming the citizens to become functionally literate (Rebusa et al, 2022). Moreover, NCLB Policy acknowledges the importance of sustainable development.…”
Section: Empowerment Of Philippine Literacy Education Through No Chil...mentioning
confidence: 99%
“…Also, the technical assistance on the manipulation of the handson use of the technologically based resources had been quietly monitored by the school administrations. Findings from the study "Looking at the No Child Left Behind Policy: The Implementers' Perspective," by Rebusa et al (2022), revealed that teachers typically said that the "No Child Left Behind Policy" created a load https://journals.e-palli.com/home/index.php/ajet Am. J. Educ.…”
Section: Overall Mean 416mentioning
confidence: 99%
“…Based on the findings, it implies that the implementers have indicated that the NCLB policy needs financial support from school administration for it to be fully implemented. Accordingly, there must be a review of the school budget financially to look at the teacherimplementers view and their roles in the implementation of the NCLB policy for its improvement since the policy stipulated that there was financial assistance to local educational agencies (Rebusa et al, 2022). No student would be left behind, according to the Department of Education, following President Rodrigo Duterte's signature of the Alternative Learning System Law.…”
Section: Strongly Agreementioning
confidence: 99%
See 1 more Smart Citation